2018
DOI: 10.11591/ijece.v8i4.pp2319-2326
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey on Exiting Solution Approaches towards Security and Privacy Requirements of IoT

Abstract: <em>‘Internet of Things (IoT)’</em>emerged as an intelligent collaborative computation and communication between a set of objects capable of providing on-demand services to other objects anytime anywhere. A large-scale deployment of data-driven cloud applications as well as automated physical things such as embed electronics, software, sensors and network connectivity enables a joint ubiquitous and pervasive internet-based computing systems well capable of interacting with each other in an IoT. IoT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The security breach impacts on data loss and it can extend into the areas of human and physical risks. Thus, it is essential to have a security solution that should address the various issues related to the security and privacy of the data shared between entities involved in the IIoT sectors [17,18].…”
Section: Security Requirements For Iiot Landscapementioning
confidence: 99%
“…The security breach impacts on data loss and it can extend into the areas of human and physical risks. Thus, it is essential to have a security solution that should address the various issues related to the security and privacy of the data shared between entities involved in the IIoT sectors [17,18].…”
Section: Security Requirements For Iiot Landscapementioning
confidence: 99%
“…In the year 2014, a study by Hewlett-Packard revealed that 70 per cent of the most commonly used IoT devices contain serious vulnerabilities. The authors in (Chetan and Shahabadkar, 2018) discussed the various existing security challengesinteroperability, resource constraints, privacy protection and scalability. Therefore, security in IoT is the biggest concern at present and needs the attention of researchers.…”
Section: Security Challengementioning
confidence: 99%
“…These devices are compact and small, thing that makes convenient to use. There are currently billions of connected objects in the world (IoT) [1]. Mobile devices typically have limited resources, such as limited battery power and local CPU capacity, and may therefore suffer from an unsatisfactory computing experience.…”
Section: Introductionmentioning
confidence: 99%
“…Then, according to (1) and 3and if we note Λ = ∑ =1 , the total execution time can be formulated as:…”
Section: Introductionmentioning
confidence: 99%